Recent advances quantifying the large wood dynamics in river basins: New methods and remaining challenges - Ruiz-Villanueva, V.; Piégay, H.; Gurnell, A. A.; Marston, Richard A.; Stoffel, M. (My University, 2016)
Large wood is an important physical component of woodland rivers and significantly influences river morphology. It is also a key component of stream ecosystems. However, large wood is also a source of risk for human activities as it may damage infrastructure, block river channels, and induce flooding. Therefore, the analysis and quantification of large wood and its mobility are crucial for understanding and managing wood in rivers. As the amount of large-wood-related studies by researchers, river managers, and stakeholders increases, documentation of commonly used and newly available techniques and their effectiveness has also become increasingly relevant as well. Important data and knowledge have been obtained from the application of very different approaches and have generated a significant body of valuable information representative of different environments. This review brings a comprehensive qualitative and quantitative summary of recent advances regarding the different processes involved in large wood dynamics in fluvial systems including wood budgeting and wood mechanics. First, some key definitions and concepts are introduced. Second, advances in quantifying large wood dynamics are reviewed; in particular, how measurements and modeling can be combined to integrate our understanding of how large wood moves through and is retained within river systems. Throughout, we present a quantitative and integrated meta-analysis compiled from different studies and geographical regions. Finally, we conclude by highlighting areas of particular research importance and their likely future trajectories, and we consider a particularly underresearched area so as to stress the future challenges for large wood research. ©2016. American Geophysical Union.
Citation: Ruiz-Villanueva, V., Piégay, H., Gurnell, A. A., Marston, R. A., & Stoffel, M. (2016). Recent advances quantifying the large wood dynamics in river basins: New methods and remaining challenges. Reviews of Geophysics. doi:10.1002/2015RG000514
Keywords: (Large Wood) Budgeting; (Large Wood) Mobility; (Large Wood) Tracking Techniques; (Large Wood) Transport Modeling; (Large Wood) Transport Rate; Riparian Vegetation